Corneal confocal microscopy and dry eye findings in contact lens discomfort patients. Issue 1 (February 2018) - Dogan, Aysun Sanal; Gurdal, Canan; Arslan, Nese
Abstract: Objectives: To evaluate the corneal confocal microscopy and dry eye findings in patients with contact lens discomfort. Methods: The study included 3 groups of participants: Contact lens wearers using silicone hydrogel soft contact lenses who are symptomatic (CLD, n = 15) or asymptomatic (ACL, n = 11) and non-wearers as controls (n = 14). Duration of contact lens wear, Ocular Surface Disease Index (OSDI) questionnaire responses, fluorescein tear break-uptime (FBUT), and corneal confocal microscopy findings were recorded. Results: Mean age was 25.7 ± 8.2 years and male/female ratio was 7/33. Demographic findings were similar regarding the groups. CLD patients had a longer lens use history than ACL (median 5 vs 2 years, p < 0.001). OSDI scores were higher in CLD group than ACL or controls (p < 0.001, p = 0.002). FBUT was significantly lowest in CLD group, compared to controls and ACL (p < 0.001, p = 0.039). FBUT was also lower in ACL patients compared to controls (p = 0.036). There was no difference between basal epithelium cell counts between all 3 groups. Anterior stromal activated keratocyte numbers were similar between contact lens using groups but was lower in controls (p = 0.005). However, dendritiform cells in the sub-basal nerve layer were higher in CLD group compared to controls but similar to ACL (p < 0.001, p = 0.058). Graded sub-basal nerve tortuosity was more prominent in CLD group than the ACL (p = 0.014). Conclusion: Patients with CLD had been wearing contact lenses for longer than those without symptoms. OSDI and FBUT scores were worse in CLD patients. In contact lens discomfort patients, there were increased dendritiform cells, indicating intensified inflammatory status of the cornea.